HETEROGENEO-CATALYTIC SYNTHESIS OF VINYL CHLORIDE AND CHLOROPRENE FROM ACETYLENE - Akmalaiuly K.,; Fayzullayev N., (Academic Scientific Journal of Chemistry, 2020)
For the catalytic hydro chlorination of acetylene in the vapor phase based on local raw materials for the Zola-gel technology, we selected an active and high-performance catalyst (ZnCl2)x*(FeCl3)y*(CuCl2)z and also under the influence of various factors (partial pressure, temperature, ratio of reagent properties, contact time, catalyst concentration) the yield and reaction rate were studied with the participation of the selected catalyst. Based on the results obtained, a kinetic equation was proposed that satisfies the reaction, its adequacy is estimated, and a scheme of the reaction mechanism and the basis on the kinetic model are proposed. Because of studying the influence of the mass transfer coefficient on the process productivity and the influence of other factors, the technological parameters of the catalytic flocculants of vinyl chloride and the chloroprene extraction reactor of acetylene were calculated and the main indicators of the compatibility of technological capabilities of environmental and economic factors were substantiated. The successful development of the production of VC from ethylene was associated with the search for a cheaper hydrocarbon feed than acetylene. Analysis of the structure of the cost price of VC obtained by various methods shows that the acetylene method gives the highest cost, with acetylene accounting for about 90%. However, the world hydrocarbon price environment is constantly changing. In the future, it is possible to increase prices for oil and gas raw materials, the convergence of prices for acetylene and ethylene, and the latter may lose its main advantage in this regard.